Oxygen mediates vascular smooth muscle relaxation in hypoxia. - Jessica Dada; Andrew G Pinder; Derek Lang; Philip E James (PLoS ONE)
The activation of soluble guanylate cyclase (sGC) by nitric oxide (NO) and other ligands has been extensively investigated for many years. In the present study we considered the effect of molecular oxygen (O2) on sGC both as a direct ligand and its affect on other ligands by measuring cyclic guanosine monophosphate (cGMP) production, as an index of activity, as well as investigating smooth muscle relaxation under hypoxic conditions. Our isolated enzyme studies confirm the function of sGC is impaired under hypoxic conditions and produces cGMP in the presence of O2, importantly in the absence of NO. We also show that while O2 could partially affect the magnitude of sGC stimulation by NO when the latter was present in excess, activation by the NO independent, haem-dependent sGC stimulator 3-(5'-hydroxymethyl-2'-furyl)-1-benzylindazole (YC-1) was unaffected. Our in vitro investigation of smooth muscle relaxation confirmed that O2 alone in the form of a buffer bolus (equilibrated at 95% O2/5% CO2) had the ability to dilate vessels under hypoxic conditions and that this was dependent upon sGC and independent of eNOS. Our studies confirm that O2 can be a direct and important mediator of vasodilation through an increase in cGMP production. In the wider context, these observations are key to understanding the relative roles of O2 versus NO-induced sGC activation.